(untitled) (European Journal of Pure and Applied Mathematics, 2024)
The aim of this paper is twofold. Firstly, we obtain expressions of the degenerate moments of a discrete nonnegative integer valued random variable. Secondly, we get an expression for the expectation of any monomial in discrete nonnegative integer-valued random variables.